PENERAPAN DATA MINING UNTUK KLASIFIKASI PRODUK MERK BATA MENGGUNAKAN ALGORITMA K-MEANS - Hernita Samosir; Muhammad Amin; Indra Ramadona Harahap (LPPM STMIK Royal Kisaran, 2021)
AbAbstract: Tanjungbalai Bata Store is a store that is engaged in the business of selling products and every day processes purchase data, sales data and transaction data. Transaction data is the result of sales that can be obtained so that store management knows the strategies that will be carried out to increase sales results. As for consumers who make transactions at stores for a separate reason, especially because of the completeness and many models that can be obtained from the Tanjungbalai brick shop, another reason is that the Tanjungbalai Brick Shop can provide a sense of comfort and peace in addition and the cleanliness seen from the store . There are many types of products sold at the Tanjungbalai Brick Shop. However, Tanjungbalai Brick Shop cannot classify products that are selling well and those that are not selling well. So that the difficulties experienced are the frequent shortage of stock of products that sell well because sales are high and the accumulation of products that are not selling well in the warehouse because the sellers are low. Based on the problems above, data mining is needed to classify which products are in demand and which are not. Data mining and k-means methods can help in this research combined with the PHP programming language and MySQL database. Keywords:Data Mining; Product Classification; K-Means Algorithm. Abstrak:Toko Bata Tanjungbalai adalah toko yang bergerak di bidang bisnis penjulalan produk dan setiap harinya melalukan proses data pembelian, data penjualan maupun data transaksi. Data transaksi merupakan hasil penjualan yang di dapat agar manajemen toko mengetahui strategi yang akan di lakukan untuk meningkatkan hasil penjualan. Adapun konsumen yang melakukan transaksi di toko memiliki alas an tersendiri ataupun di karenakan kelengkapan dan banyak model yang bisa di dapatkan dari toko bata tanjungbalai, alasan yang lain adalah Toko Bata Tanjungbalai dapat memberikan rasa nyamandan tentram di tambah lagi keramahan dan kebersihan yang di lihat dari toko tersebut. Ada banyak jenis produk yang terjual di Toko Bata Tanjungbalai, namun toko bata Tanjungbalai tidaklah mampu dalam membagikan kelompok produk tersebut masuk kategori laris dan tidak laris. Sehingga kesulitan yang dialami yaitu seringnya kekurangan stok produk yang laku karena penjualannya tinggi dan menumpuknya produk yang tidak laris di gudang karena penjualnnya rendah. Berdasarkan permasalahan di atas maka dibutuhkan data mining untuk mengelompokkan produk mana saja yang laris dan tidak. Data mining dan metode k-meansdapat membantu dalam penelitian ini dipadukan dengan pemrograman PHP dan MySQL. Kata Kunci :Data Mining; Klasifikasi Produk; Algoritma K-Means